Juridical Analysis of Sale and Purchase Lawsuits Conducted by Foreigners Using the Name of Indonesian Citizens (Study of Decision Number 157/PDT/2021/PT DPS) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This problem was studied from a legal point of view. The plaintiff felt materially and immaterially disadvantaged because the selling price of the disputed object was not by the market price, and the defendant sold the disputed object to Defendant II without the knowledge of the plaintiff as the funder. To obtain justice and legal certainty the plaintiff filed a lawsuit at the Denpasar District Court to get justice. Based on the exposure. The basis for the judge's legal considerations in decision Number: 157/PDT/2021/PT DPS Because in canceling the nominee agreement between the plaintiff and the defendant, the panel was only of the opinion that it did not have legal certainty, while legally the nominee agreement has been regulated by the prohibition in Law Number 25 of 2007 concerning Capital Investment and it is reaffirmed regarding the sale and purchase of land rights in Law Number 05 of 1960 in article 21, namely that Indonesian citizens are prohibited from having land ownership rights, then the nominee agreement between the Plaintiff and Defendant I is declared void because it conflicts with the provisions of article 1337 of the Civil Code and the sale and purchase agreement between defendant I and Defendant II is valid. Therefore, the author disagrees with what the Denpasar district court judge decided.